A matter of principle ; humanitarian arguments for war in Iraq - Cushman, Thomas, 1959- (University of California Press, 2005)
Current debate over the motives, ideological justifications, and outcomes of the war with Iraq have been strident and polarizing. A Matter of Principle is the first volume gathering critical voices from around the world to offer an alternative perspective on the prevailing pro-war and anti-war positions. The contribu-tors - political figures, public intellectuals, scholars, church leaders, and activists - represent the most powerful views of liberal internationalism. Offering alternative positions that challenge the status quo of both the left and the right, these essays claim that, in spite o.